2018
DOI: 10.1007/s11457-018-9221-3
|View full text |Cite
|
Sign up to set email alerts
|

The Beginning of the Viking Age in the West

Abstract: During the Viking Age, Arctic Scandinavia was a source of exquisite furs, down, walrus ivory, and other commodities that met with high demand in England and on the Continent. Hitherto, the earliest firm evidence of this trade has been Ohthere's account c. 890, but in light of this paper's findings, its history may be pushed further back in time. Geological analyses of whetstones retrieved in eighth-to early ninth-century Ribe, southwestern Jylland, in present-day western Denmark, demonstrate that the majority … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 34 publications
2
22
0
1
Order By: Relevance
“…Second, concerning the importance of maritime communication, the distribution analysis has shown that most of the early Insular finds are found in areas along the Nordvegr , which indicates early maritime mobility and sometimes early links with urban networks further south in Scandinavia. This observation is in accordance with Sindbæk's (2011) and Baug et al’s (2018) suggestions that pre-Viking journeys to such urban markets may have facilitated the movement of knowledge and improved maritime mobility, which ultimately led to the Viking expansion.…”
Section: Environmental Knowledge and The Earliest North Sea Crossingssupporting
confidence: 89%
See 3 more Smart Citations
“…Second, concerning the importance of maritime communication, the distribution analysis has shown that most of the early Insular finds are found in areas along the Nordvegr , which indicates early maritime mobility and sometimes early links with urban networks further south in Scandinavia. This observation is in accordance with Sindbæk's (2011) and Baug et al’s (2018) suggestions that pre-Viking journeys to such urban markets may have facilitated the movement of knowledge and improved maritime mobility, which ultimately led to the Viking expansion.…”
Section: Environmental Knowledge and The Earliest North Sea Crossingssupporting
confidence: 89%
“…Likewise, Baug et al (2018) have recently shown how there was a 'steady supply' of 'Mostadmarka' type whetstones from Trøndelag to markets in southern Scandinavia from at least the early eighth century. These results also suggest increasing economic activity in the North Sea area which drew large parts of Norway into supra-regional networks in the decades before and after the first recorded Viking attacks (as underlined by Myhre, 1993, andBaug et al, 2018). Frisian Tating ware is found as far north as Borg in Lofoten (Holand, 2003: 203-09), and seventh-and eighth-century Frankish coins were recently recovered in excavations at Ranheim, Trøndelag (Grønnesby & Heen-Pettersen, 2015: 176).…”
Section: Finds Distribution and The Significance Of The Nordvegrmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, research into Viking Age ( c. ad 790–1050) society has explored its complex social compositions, group formations, and social identities (Svanberg, 2003; Downham, 2009; Raffield et al, 2016). The reassessments of object-based, chronological frameworks (Skibsted Klæsøe, 1999) and new dating of trade patterns and maritime ventures (Ashby et al, 2015; Price et al 2016; Baug et al, 2018) have furthermore shown that the early Viking Age comprises multifaceted and overlapping sets of processes and events that extend back to the early eighth century. One illustrative example of this long overlap is the change in jewellery sets from around ad 700 on the Scandinavian peninsula, including large disc-on-bow brooches, arm-rings, and the introduction of domed, oblong brooches (Callmer, 1984: 67).…”
Section: Introductionmentioning
confidence: 99%